Social Media Affect on Contemporary Design for Architect and Client via Instagram Sites - Imam Baihaqi Kosasih; Muhammad Abdul Gahar Sangaras (International Journal of Research and Applied Technology (INJURATECH), 2022)
The development of information technology, especially social media, not only has an impact on changing the behavior of its users, but also brings changes in various fields. The high intensity of human activity on social media can no doubt change the lifestyle of its users, including influencing the design of their dwellings. This phenomenon is expected to be used especially for architects to open up new opportunities in getting their clients. This study uses a qualitative method with a library research approach. This study displays scientific reasoning related to the development of social media which can have an impact on changes in work process patterns and the final result of a contemporary design work in the world of architecture. Like a client's request who plans a contemporary residential design following trends on social media, one of which is Instagram. Instagram is the third most used social media platform in the world. This is very effective for architects and prospective clients by utilizing social media to see references to the design of the building they want to plan. It is certain that the rapid development of social media information technology, especially Instagram, can affect the world of residential design.